An Analysis of Embedded Clauses in Sidney Sheldon's NOTHING LASTS FOREVER” And Their Translation in Indonesian - Anshori, Adam (English Education Department, Universitas Islam Indonesia, 2007)
This research aims at describing how the English embedded clauses lexicogrammatically realized in the HI version of the novel, to discover the interpretation of the English-BI embedded clause representations in the context of language variations of novel texts, and to count the percentage of each class of English embedded clauses with relative pronouns and their translation in BI.This research applies a descriptive method it means that the researcher only collects the data, analyzes them and draws conclusions from the analyzed data. The source of the data consists of the novel Nothing Lasts Forever by Sidney Sheldon and its translation in Indonesian Tiada Yang Abadi by Hendarto Setiadi. A sample of 91 relative pronouns was established using the purposive sampling technique.The findings of the study show that 89.01% of the English embedded clauses with relative pronouns are translated into BI relative pronoun yang. There are also English embedded clauses which are translated with BI words other than yang and English embedded clauses with relative pronouns which have no equivalents in Indonesian, Their percentages are 6.59% and 4.39%.The English embedded clauses with relative pronouns which are translated into BI words other than yang are classified into 3 types. English embedded clauses with relative pronouns translated into 1)conjunction, 2)prepositionand3) other equivalent word in BI. There are also3 types of English embedded clauses with relative pronouns which have no equivalent in BI. They are 1) English relative pronouns which have no equivalent in BI, 2) English embedded clauses which have no equivalent in BI and 3) The whole sentence which has an English embedded clause in it has no equivalents in BI. The translator may also change the complexity of some sentences by changing complex sentences into compound ones, and thus made them more readable.